Human Resources Information System (HRIS) to enhance civil servants' innovation outcomes: Compulsory or complimentary? - Evi Satispi; Ismi Rajiani; Mamun Murod; Andriansyah Andriansyah (Administrative Sciences, 2023)
The Internet of things (IoT) has oriented organisations digitally in administrating human resources. In line with this trend, Indonesian public sectors are adopting Human Resources Information Systems (HRIS) to boost employee innovation outcomes. However, coercive pressure to implement HRIS has only resulted in fiascos for the technology, which cannot be fully considered to eliminate long, ineffective, and inefficient practices. This study examines the instrumental adoption factors to adopt HRIS in boosting employee innovation outcomes from technological, organisational, people, and social outlooks. The empirical data consisting of 500 valid datasets were obtained from public servants in Indonesia via web-based questionnaires. structural equation modelling (SEM), which was used to examine the relationship among constructs. Technology fit, organisational resources, knowledge, and social influences have positive impacts on technology adoption. However, when treated as a mediation, the negative path from HRIS to innovation outcomes implied that e-HRM reflected in HRIS implementation would not make employees innovative. The scrutinized under ability, motivation, and opportunity (AMO) framework and empirical insights clearly portray that Indonesian's ability to fit into this framework is problematical, making technological innovation in the Indonesian public sector only complimentary, not compulsory. This study suggests that HRM reform in public organisations is a top priority if the country wishes to achieve world-class bureaucracy by 2025.
Keywords: 350; HRIS; Indonesia; public servants; technology